Quantification of match and training workload by position in Korean professional men’s volleyball players - Munku Song; Sewoon Yoon; Sangcheol Yoo; Hyunsik Kang (Journal of Men's Health)
This research aimed to quantify match workload by position among Korean Men’s Professional Volleyball League (KOVO) players during the regular season. A secondary aim was to provide information about the workload requirements during pre-match warm-up and training sessions. This study involved three liberos (L), three setters (S), eight outside or right-side hitters (OH/RS) and five middle blockers (MB). Playing minutes (PM), total jumps, low-band jumps, medium-band jumps, high-band jumps, explosive efforts (EE) and repeated high-intensity efforts (RHIE) were objectively quantified as external workloads through a wearable activity monitor. During matches, S had the highest loads of total jumps (p < 0.001) and medium-band jumps (p < 0.001). MB performed the most high-band jumps (p < 0.001) with the highest EE (p < 0.001) and RHIE (p < 0.001). PM was shorter in training than in matches for all positions, but variables like medium-band jumps, EE and RHIE were higher in training compared to matches. S had the highest pre-match workload for total, low and medium band jumps (p < 0.001, p < 0.001 and p < 0.001, respectively). OH/RS had the highest high-band jumps (p < 0.001), while L had the highest load for EE (p < 0.001) and RHIE (p < 0.001). Our findings indicate that volleyball workload demands differ by position during matches and pre-match warm-ups, underscoring the importance of designing position-specific training programs.